High-Risk Factors for Depression in Women before Performing an Elective Termination of Pregnancy: A Prospective Study - Jing Li; Yanhua Zhang; Zhiyun Zhang; Haixia Zhang; Meilian Xie; Li Li; Wei Yi; Meiliing Chen (Clinical and Experimental Obstetrics & Gynecology)
Background: As the phenomenon becomes increasingly prominent, the medical community is paying more and more attention to the health of women with elective termination of pregnancy. This study investigated the incidence of preoperative pre-abortion and its high-risk factors in elective termination of pregnancy women. Health interventions were used to reduce the incidence of such pre-abortion, and targeted to the post-abortion care. Methods: Using a convenient sampling method, 170 women who elected to terminate pregnancy in the gynecological clinic of Beijing Ditan Hospital from 1 June 2019 to 1 June 2020 were selected. A questionnaire in two parts was used as a research tool. General information collected mainly included the presence or absence of sexually transmitted diseases, age, address, education, economic level, occupation, etc., as well as the self-measurement Self-rating Depression Scale (SDS) for pre-abortion. Results: The average SDS score of 170 women who have elective termination of pregnancy was 51.2 ± 11.7. With a SDS score ≥53 points in 75 patients, the incidence of depression was 44.1% (75/170). Factors associated with depression were patient age (p = 0.002), education level (p = 0.040), and the man’s refusal for use of contraception during sexual intercourse (p = 0.000). Conclusions: Our research suggests that younger age, lower education, and inactive use of male contraception during sex are risk factors for pre-abortion in women with abortion. Physicians should consider these findings for early detection of pre-abortion and timely intervention for such women.